KESENJANGAN ANTARA PERSEPSI DAN HARAPAN MAHASISWA PADA KEGIATAN TUTORIAL TATAP MUKA MATA KULIAH PRAKTIKUM IPA SD - Sandra Sukmaning Adji; Isti Rokhiyah (LPPM Universitas Terbuka, 2011)
Learning subject such as Natural Sciences (IPA) is not only learns about science concepts but also experiencing the real nature. This study aims to obtain information about students' perceptions on the content of science laboratory practices, the preparation of students in tutorials, as well as expectations for practical implementation of IPA. Questionnaires were administered by mail and direct delivery. A total of 399 students from Medan, Jakarta, Jakarta, Samarinda, Surabaya, Bangka Belitung, Mataram, Palu, which registered to the course at Universitas Terbuka (UT) in the first semester of 2009 had answered. Observation was carried out at 4 locations in Sukabumi, Depok, Tangerang, and Cibarusa. The results indicated that independent laboratory practices were done more compared to the formal tutorial practices. Perceptions of students towards science laboratory activities of the of 4 scale (poor (1), fair (2), average (3) and good (4)), were respectively X = 3.34 for student involvement in laboratory practices, X = 3.01 for the content material, X = 3.27 for the presence of tutors, and X = 2.61 for the availability of facilities and infrastructure. While the gap between the conditions and expectations of students in consecutive tutorial activities was 0.71 for the availability of facilities and infrastructure, 0.41 for to the availability of laboratory practice materials, 0.31 for the competence of tutors, and 0.33 for student involvement in laboratory practice activities.